2004
DOI: 10.1038/sj.npp.1300655
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cannabinoid Neurotransmission Augments the Extinction of Conditioned Fear

Abstract: The endogenous cannabinoid (eCB) system represents a major therapeutic target for the treatment of a variety of anxiety-related disorders. A recent study has demonstrated that pharmacologic or genetic disruption of CB1-receptor-mediated neurotransmission decreases the extinction of conditioned fear in mice. Here, we examined whether CB1 blockade would similarly disrupt extinction in rats, using fear-potentiated startle as a measure of conditioned fear. We also examined whether pharmacologic enhancement of CB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
253
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(283 citation statements)
references
References 47 publications
27
253
2
1
Order By: Relevance
“…Consequently, we evaluated whether OL-135 administered only before each extinction trial would facilitate this process, and showed that elevated levels of FAAs were only required during the extinction trials themselves. This effect is consistent with a recent report in which AM404, a purported inhibitor of the putative anandamide transporter that also inhibits FAAH (Beltramo et al, 1997;Jarrahian et al, 2000;Glaser et al, 2003;Hillard and Jarrahian, 2005) potentiated extinction of a conditioned fear response (startle) in rats (Chhatwal et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consequently, we evaluated whether OL-135 administered only before each extinction trial would facilitate this process, and showed that elevated levels of FAAs were only required during the extinction trials themselves. This effect is consistent with a recent report in which AM404, a purported inhibitor of the putative anandamide transporter that also inhibits FAAH (Beltramo et al, 1997;Jarrahian et al, 2000;Glaser et al, 2003;Hillard and Jarrahian, 2005) potentiated extinction of a conditioned fear response (startle) in rats (Chhatwal et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…However this interpretation is somewhat limited by the fact that SR141716 given alone delayed extinction. As previously described in a similar water maze task (Varvel et al, 2005a) and in conditioned fear paradigms (Marsicano et al, 2002;Suzuki et al, 2004;Chhatwal et al, 2005), SR141716 robustly attenuated extinction in the present experiment. The effect of SR141716 presented here replicates our previously published report, with some minor procedural differences such as the weekly extinction trials (as opposed to bi-weekly trials) and the inclusion of the quadrant data.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It has been suggested that the apparent facilitation of extinction by cannabinoid agonists or reuptake inhibitors is in fact due to an impairment of memory reconsolidation by these compounds, 236 although it is somewhat difficult to compare this study to that of Chhatwal 234 because of the different routes of administration employed (systemic vs intra-amygdala) as well as the finding of a significant effect of WIN 55,21202 in one case 236 and not the in other. 234 Kamprath et al 237 have argued that endogenous cannabinoids modulate nonassociative learning processes including habituation, and are involved in fear extinction only to the extent that habituation is a component of extinction. That is, endogenous cannabinoid release is not a mechanism of fear extinction per se but rather occurs under conditions in which habituation occurs, which include, but are not specific to, extinction.…”
Section: Neurotransmitter Systemsmentioning
confidence: 82%
“…The impairment of LTDi was mimicked in slices obtained from wild-type mice and superfused with SR141716A. Impairment of fear extinction by pre-extinction training administration of SR141716A has been reported by several other groups as well 168,234,235 Chhatwal et al, 234 in a study of extinction of fearpotentiated startle in rats, examined SR141716A as well as positive modulators of cannabinoid neurotransmission. The CB1 agonist WIN 55,212-2 had no effect on extinction retention when administered systemically before extinction training, but AM404, an inhibitor of cannabinoid reuptake and enzymatic degradation, dose-dependently facilitated extinction retention measured 1 and 24 h after extinction training and impaired subsequent reinstatement following exposure to unsignaled footshock.…”
Section: Neurotransmitter Systemsmentioning
confidence: 92%